2009
DOI: 10.17221/597-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vintage on Cu, Fe, Zn and Pb Content in Some Croatian Red Wines

Abstract: Knowledge of the content of heavy metals is important because of their impact on the wine stability or on the health of the consumers. The presence of heavy metals in wines is a consequence of an action of various factors such as conditions of the cultivation and processing of grapes and production, stabilisation or storage of wine. In this work determination of heavy metals (Cu, Fe, Zn and Pb) content in red wines was carried out. Selected wine was Plavac mali, Croatian autochthonous sort, produced by various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
18
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 6 publications
7
18
1
Order By: Relevance
“…These results present mean values for the three measurements performed for each sample. The results of the analyses are summarised in Tables 6-8. A high dispersion of the contents of the elements observed in wines was also described in the literature (Núñez et al 2000;Banović et al 2009;Şen & Tokatli 2014). Our results showed that the mineral compositions of wine and soils were interrelated.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…These results present mean values for the three measurements performed for each sample. The results of the analyses are summarised in Tables 6-8. A high dispersion of the contents of the elements observed in wines was also described in the literature (Núñez et al 2000;Banović et al 2009;Şen & Tokatli 2014). Our results showed that the mineral compositions of wine and soils were interrelated.…”
Section: Resultssupporting
confidence: 68%
“…A number of factors affecting the mineral content of wines have been reported, including mineral composition of soil, viticultural practices, environmental factors, fermentation process and the procedure of storage conditions (Fernandez 1988;Núñez et al 2000;Marini et al 2006). The metal content in wine is important due to their effect on the wine quality and on the health of consumers (Núñez et al 2003;Banović et al 2009). Moreover, there are numerous factors influencing the metallic constituents of wine, such as specific production area, grape varieties, soil and climate, and wine-making process (Núñez et al 2003).…”
mentioning
confidence: 99%
“…The results obtained are in a good agreement with those previously reported for Macedonian wines (Karadjova et al 2007) and Brazilian wines (Freschi et al 2001). In addition, Macedonian wines presented lower amounts of Pb (on average 16.9 μg/L) compared to data for Croatian wines reported by Tariba et al (2011) (on average 33 μg/L) and Banović et al (2009) (on average 197 μg/L), as well as lower compared to Serbian wines (Ražić et al 2007), Ethiopian white wines (Woldemariam and Chandravanshi 2011) and wines from the Korean market (Kim 2004). In fact, Pb is a toxic heavy metal with widespread industrial uses and no nutritional benefits are Fig.…”
Section: Elemental Characterization Of Winescontrasting
confidence: 54%
“…Electrothermal atomic absorption spectroscopy (ETAAS) technique is not suitable for fast multielement analysis, but this technique offers high sensitivity and selectivity for determination of low levels of metals, and therefore, it is suitable and widely used for determination of Pb and Cd at low levels (Edel et al 1995;Cvetković et al 2006;Banović et al 2009;Tariba et al 2011). Furthermore, this technique allows direct determination of Pb and Cd in wine samples, which is advantageous for routine analyses, saving time and requiring minimum sample preparation (Bruno et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Methods described so far include atomic absorption spectrometry (3,12,13), inductively coupled plasma optical emission spectrometry (14), inductively coupled plasma mass spectrometry (15,16), energy dispersive X-ray fl uorescence (17), potentiometric stripping analysis, and differential pulse anodic stripping voltammetry (13,18). The most common among them for determining Pb at trace levels is graphite furnace atomic absorption spectrometry (GFAAS) (14,(19)(20)(21)(22), a selective, simple, and highly sensitive method, adequate for direct determination in various matrices.…”
mentioning
confidence: 99%